Rehabilitation of peg shaped lateral incisors with ceramic veneer: A case report - Shrestha, M.; Joshi, S. P.; Shrestha, P.; Sah, S.; Verma, A. (Journal of Nepalese Prosthodontic Society, 2021)
The most common discrepancy concerning tooth size is the presence of peg shaped lateral incisors, which can cause teeth with reduced size, anterior diastema and consequently an unpleasant smile. The development of adhesive dentistry and ceramic veneers allowed all ceramic bonded restorations to become an esthetic, durable and functional approach to reestablish the smile harmony.The purpose of this clinical report is to describe a conservative treatment approach using ceramic veneer to restore an esthetic disharmony caused by bilateral peg shaped lateral incisors.